Bombiscardovia coagulans gen. nov., sp. nov., a new member of the family Bifidobacteriaceae isolated from the digestive tract of bumblebees - Killer, J; Kopečný, J; Mrázek, J; Havlík, J; Koppová, I; Benada, O; Rada, V; Kofroňová, O (Systematic and applied microbiology, 2010)
One hundred and eighty-seven fructose-6-phosphate phosphoketolase positive strains were isolated from the digestive tract of three different bumblebee species. Analyses of the partial 16S rRNA gene sequences of the representative strains showed only 92.8% and 92.5% similarity to Bifidobacterium coryneforme YIT 4092(T) and Bifidobacterium indicum JCM 1302(T), 92.2% similarity to Alloscardovia omnicolens CCUG 18650 and slightly reduced similarity of 91% to other members of the family Bifidobacteriaceae. On the other hand, analyses of the partial heat-shock protein 60 (hsp60) gene sequence revealed that the proposed type strain BLAPIII-AGV(T) was affiliated only to the 60 kDa chaperonin sequence of uncultured bacteria from human vagina (79-80%) and the hsp60 gene sequence of A. omnicolens CCUG 31649(T) (75.5%). The peptidoglycan type was A4α with an l-Lys-d-Asp interpeptide bridge. The polar lipids contained diphosphatidylglycerol, an unknown phospholipid, six glycolipids and two phosphoglycolipids. The major fatty acids were C(18:1), C(20:0) and C(18:0). These and other analyses indicated that the isolates represented a new genus within the family Bifidobacteriaceae. This observation was further substantiated by determination of the DNA G+C contents (46.1-47.1 mol%). Affinity of the strains to some scardovial genera (Aeriscardovia, Alloscardovia and Metascardovia) was also confirmed by their ability to grow under aerobic conditions. Besides the above mentioned differences, Bombiscardovia coagulans was found to differ from all scardovial genera in the ability to grow at temperatures as low as 5°C, which was another major phenotypically different characteristic of this new member of the family Bifidobacteriaceae. Hence, on the basis of phylogenetic analyses using partial 16S rRNA and hsp60 gene sequence data, and the temperature related phenotypic difference, we propose a novel taxa, B. coagulans gen. nov., sp. nov. (type strain=BLAPIII-AGV(T)=DSM 22924(T)=ATCC BAA-1568(T)).
Keywords: DNA bakterií; sekvence nukleotidů; druhová specificita; Phylogeny; chaperon hsp60; techniky typizace bakterií; Actinobacteria; Molecular Sequence Data; Sequence Analysis, DNA; molekulární sekvence - údaje; Chaperonin 60; zastoupení bazí; Aldehyde-Lyases; nízká teplota; aldehydlyasy; lipidy; RNA ribozomální 16S; Phenotype; zvířata; Base Composition; včely; RNA, Ribosomal, 16S; Cold Temperature; sekvenční analýza DNA; Peptidoglycan; DNA, Bacterial; mastné kyseliny; Base Sequence; Bees; fylogeneze; fenotyp; Lipids; Species Specificity; Bacterial Typing Techniques; Animals; Gastrointestinal Tract; peptidoglykan; gastrointestinální trakt; Fatty Acids